(untitled) (International Research in Social Sciences, 2026)
William James’s idea that "the breaches between such thoughts are the most absolute breaches in nature" has aroused various discussions and caused difficulty to understand it. This paper aims to provide a more thoroughgoing account for this idea by deeply explore its connotations. In his theory of The Stream of Thought, he divides the stream of thought into substantive parts and transitive parts. The former, substantive parts, usually contain knowledge principles and vivid sensory experiences, and mostly are expressed by our words. The latter, transitive parts, on the other hand, are the dynamic connections between thoughts, difficult to grasp directly, carrying thought relations, and having unique tendencies and forms. By doing so, James emphasized the personal nature of thoughts, but he never cuts off the possibility of interpersonal understanding. Based on this, this article further divides the content of thoughts into "inside" and "outside" parts to understand James’s idea appropriately and points out that we can narrow the breaches between thoughts through imagination and language communication. Imagination helps us empathize with others’ inside thoughts, and language, as a communication tool, enables the sharing of outside thoughts. Although James emphasized the complexity of the thought process and the significance of individual subjective activities, making it difficult to fully understand others’ thoughts, the similar interests, concerns, communication tools among humans still provide possibilities for mutual understanding.